Serotonin receptor gene HTR3A variants in schizophrenic and bipolar affective patients - Niesler, Beate; Weiß, Birgit; Fischer, Christine; Nöthen, Markus Maria; Propping, Peter; Bondy, Brigitta; Rietschel, Marcella; Maier, Wolfgang; Albus, Margot; Franzek, Ernst; Rappold, Gudrun (Pharmacogenetics and genomics, 2001)
Serotonin receptor genes have always been considered excellent candidate genes in the aetiology of neurogenetic diseases. In this study, we assessed sequence variations of the HTR3A gene. For this purpose, we established exon-specific primers and analysed DNA samples from 165 unrelated individuals including 70 schizophrenic patients, 48 patients with bipolar affective disorder and 47 healthy control persons using polymerase chain reaction/single-strand conformational polymorphism analysis. We discovered six sequence variants, five of which represent polymorphisms. These polymorphisms could not be associated with schizophrenia and bipolar affective disorder (P = 0.055-1). We also detected a missense mutation in exon 9 in a schizophrenic patient at a conserved position (Pro391Arg). To determine the incidence of this substitution an extended set of 358 schizophrenic patients and 155 control individuals was investigated. The Pro391Arg mutation was not detected in these schizophrenic patients and controls screened. However, a second missense mutation (Arg344His) was detected in one schizophrenic patient, but not in any of the controls. These results suggest that the observed mutations in HTR3A are rare and therefore do not play a major role in the aetiology of the disorder. Further studies are needed to support the hypothesis that HTR3A may contribute to the schizophrenia in these patients.
Gesehen am 24.03.2021